Performance analysis of probabilistic multi-path geographic routing in wireless sensor networks. (1st December 2008) - Wang, Na; Chang, Chorng Hwa
We present a theoretical performance analysis of network lifetime for sensor networks that route packets through multiple paths between a source and destination pair. Our analysis is based on the length of the paths established and we show how this value can be used to estimate the lifetime of the sensor network. Through our analysis, we show how much the network lifetime can be increased when additional paths are established between source and destination. We divide our analysis in two parts: 1) when the probability of link-level retransmission is negligible; 2) when it is significant. In the former case, we develop analytical closed-form equations that allow us to compute the expected network lifetime. In the latter case, we develop theoretical tools that allow us to compute the probability distribution function of the network lifetime and we show simulation results that confirm our theoretical analysis. We also demonstrate how to estimate the increase in network lifetime when more than one path is added. We also compute the probabilities of packet forwarding for each path that maximise the gain in network lifetime.